Optimizing irrigation for photosynthesis and drought resistance of extra- long staple cotton varieties - NING Liyun; ZHANG Jusong; WANG Li; WU Yifan; HU Haoran; ZHANG Chengjie (Guan'gai paishui xuebao)
【Objective】 Cotton is a vital cash crop in Xinjiang, but its production depends heavily on irrigation due to water scarcity in the region. This study experimentally evaluated the drought resistance of major extra-long staple (ELS) cotton (Gossypium barbadense) varieties throughout their entire growth period. 【Method】The field experiment used a two-factor split-zone design to assess the effects of three irrigation levels: W1 (3 150 m3/hm2, 70% of conventional irrigation), W2 (3 825 m3/hm2, 85% of conventional irrigation), and W3 (4 500 m3/hm2, conventional irrigation). Photosynthesis and yield responses were analyzed across different cotton varieties. The drought resistance coefficient for each variety was determined using principal component analysis, evaluating the contribution of various factors to the drought index. The comprehensive drought resistance evaluation value (D) was used to classify and assess the drought tolerance of different varieties.【Result】Both irrigation level and cotton variety significantly influenced photosynthesis, chlorophyll fluorescence traits, and yield. As irrigation decreased, the SPAD value increased, whereas the net photosynthetic rate (Pn) and chlorophyll fluorescence parameters (Fv, Fv/Fm, Fv/Fo, PIABS, and PItotal) declined. Among all varieties, Miancheng No.10 achieved the highest yield (6 806.36 kg/hm2) under W3, while Lutai 700Q produced the lowest yield (4 340.21 kg/hm2) under W1.【Conclusion】When irrigation was set at 4 500 m3/hm2, water availability had minimal impact on photosynthesis, and overall yield remained high. Among the tested varieties, Xin 78 exhibited the highest drought tolerance, while Miancheng No.10 and Xinhai No.62 were moderately drought-resistant. In contrast, Lutai 700Q was highly sensitive to drought. These findings provide insights for optimizing irrigation strategies and selecting drought-resistant ELS cotton varieties for arid regions.